2007
DOI: 10.1109/tsmcb.2007.901375
|View full text |Cite
|
Sign up to set email alerts
|

A Neuro-Fuzzy Inference System Through Integration of Fuzzy Logic and Extreme Learning Machines

Abstract: This paper investigates the feasibility of applying a relatively novel neural network technique, i.e., extreme learning machine (ELM), to realize a neuro-fuzzy Takagi-Sugeno-Kang (TSK) fuzzy inference system. The proposed method is an improved version of the regular neuro-fuzzy TSK fuzzy inference system. For the proposed method, first, the data that are processed are grouped by the k-means clustering method. The membership of arbitrary input for each fuzzy rule is then derived through an ELM, followed by a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(37 citation statements)
references
References 17 publications
0
37
0
Order By: Relevance
“…The ELM [19][20][21] is a new concept learning algorithm, which works on single hidden layer feed forward neural network (SLFN) that randomly chooses hidden nodes and the output weights of SLFN is determined analytically. The outputs are learned and updated in a single step and it really makes it as a linear network model.…”
Section: E-anfismentioning
confidence: 99%
See 1 more Smart Citation
“…The ELM [19][20][21] is a new concept learning algorithm, which works on single hidden layer feed forward neural network (SLFN) that randomly chooses hidden nodes and the output weights of SLFN is determined analytically. The outputs are learned and updated in a single step and it really makes it as a linear network model.…”
Section: E-anfismentioning
confidence: 99%
“…Based on the concept of ELM [20,21], the new e-ANFIS learning algorithm is developed. The ELM concept is used in variety of applications such as signal classifications [22][23][24], electricity forecasting [25] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Neuro-fuzzy approach is perhaps the most visible hybrid paradigm [51, [228][229][230]254, 261], realized so far, in soft computing framework. Besides the generic advantages, the neuro-fuzzy approach provides the corresponding application specific merits [76,111,120,330,368,388,394]. Rough-fuzzy [209,250,265] and neuro-rough [68,158,264] hybridizations are also proving to be fruitful frameworks for modeling human perceptions and providing means for computing with words.…”
Section: Relevance Of Soft Computingmentioning
confidence: 99%
“…In fact, fuzzy reasoning in (1) is a TS1 paradigm [14]. Test results have shown that the TS1 NF control provides more smooth control effects than a TS0 paradigm because it contains more linear consequent parameters than in the TS0 controller.…”
Section: The Adaptive Neural Fuzzy Controllermentioning
confidence: 99%
“…Once the NF control paradigm is established, its parameters should be trained properly so as to achieve optimal control performance. In this case, in each training epoch, the nonlinear system parameters of the MFs are trained by the gradient method in the backward pass, whereas the linear consequent parameters are fine-tuned by the LSE in the forward pass [14].…”
Section: The Adaptive Neural Fuzzy Controllermentioning
confidence: 99%